Gestão de águas subterrâneas transfronteiriças: Sistema Aquífero Guarani - estudo de caso - ICHIKAWA, Paulo Eiryo (2019)
This study was settled to analyze the management of transboundary groundwater, using the international cooperation activities in the Guarani Aquifer System as a study case. Thus, it analyzed the projects aimed to develop a joint management to the countries involved in the Guarani Aquifer System, reported by Borghetti , Borghetti and Rosa Filho (2005) and the World Bank (FOSTER et. al. 2009). The Agreement on the Guarani Aquifer, signed in 2010 between the four countries of the Aquifer, is also analyzed. In the first chapter, the paper presents the Guarani Aquifer, their characteristics and the activities to develop management for its transboundary waters. The theoretical fundaments to analyze relations between these countries are presented in the subsequent chapter. For this, the theoretical principles of International Relations are presented, highlighting the authors: Viotti and Kauppi (1999), Messari and Nogueira (2005), Waltz (1959) e Keohane (2005). In Chapter 4, the theoretical elements are portrayed, in an analysis of the evidence found in the case study. Conclusive aspects close this work in Chapter 5. By a multidisciplinary approach, this research was oriented as a bibliographic research, as an exploratory study. Among the documents used on this study, articles and books were consulted, for the justifications of the demand for activities involving transboundary groundwater, as well as major challenges and difficulties. From this research, it was found that the water management developed and implemented by more than one country on transboundary groundwater requires a major interest of this issue by the involved countries. Indeed, it need for a set of consolidated knowledge about these waters. Thus, on the one hand, States prioritize issues like national security and economic development, leaving issues such as the management of water resources and the environment in lower priority agenda. On the other hand, searching for more knowledge about groundwater still a challenge to the institutions involved on consolidating a joint management between countries. In this scenario, challenges to manage and learn more about this water to be discovered are hidden, just like the water still sleeping under the feet of humanity.